Plate 180: Machine for moving heavy weights - Ramelli, Agostino (Le diverse et artificiose machine del capitano Agostino Ramelli, 1588)
Mechanics: hand crank; Spur gears; worm and worm gear; lantern and crown gear.
Keywords: Machinery